2019
DOI: 10.1109/access.2019.2913172
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Rock Breaking Mechanism With Supercritical Carbon Dioxide Jet by SPH-FEM Approach

Abstract: As a novel technology in the field of petroleum exploitation, rock breaking with supercritical carbon dioxide (SC-CO 2 ) has considerable social and economic benefits. To investigate the rock breaking mechanism under SC-CO 2 jet impacting in terms of mass and energy conservation, a fluid-solid coupling numerical model was established using smoothed particle hydrodynamics (SPH) method coupled with the finite element method (FEM). Jet movement feature and the stress distribution rule of impact target were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…As the CO 2 jet shows the feature of drastic volume expansion in the free field, the SPH method is well suited for its numerical modeling [21,22]. The SPH method, which is based on the interpolation theory, allows any function to be expressed at a set of disordered points which represents particle positions via smooth kernel function.…”
Section: Theory Of Sph and Model Of Co 2 Jetmentioning
confidence: 99%
See 1 more Smart Citation
“…As the CO 2 jet shows the feature of drastic volume expansion in the free field, the SPH method is well suited for its numerical modeling [21,22]. The SPH method, which is based on the interpolation theory, allows any function to be expressed at a set of disordered points which represents particle positions via smooth kernel function.…”
Section: Theory Of Sph and Model Of Co 2 Jetmentioning
confidence: 99%
“…With the development of jet drilling technology, a large number of experts have carried out a lot of research on water jet rock breaking [16], SC-CO 2 jet rock breaking [17] and single PDC cutter cutting [18,19]. By using arbitrary lagrange eulerfinite element method (ALE-FEM) [20], SPH-FEM [21,22] and other coupled method, the simulation study of the jet rock breaking mechanism is carried out. However, there are relatively fewer researches on the composite rock-breaking of high-pressure CO 2 jet & PDC cutter, which would limit the development and application of CO 2 drilling in future exploitation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, scholars have conducted preliminary explorations on CDPTF, including CO 2 fractured coal body life cycle, crack propagation, CDPTF vibration, energy distribution, etc. Among them, the impact pressure of CDPTF on the rock body is essential.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hu et al [20] used LS-DYNA to study the rock fragmentation mechanisms when cut by a cutter and concluded that there are three fracture modes of rock breaking: forward slip, no slip and backward slip. Yang et al [21] investigated the rock-breaking mechanism under supercritical (SC)-CO 2 jet impacting based on the smoothed particle hydrodynamic finite-element method (SPH-FEM). Numerical results showed that there were two failure forms for rock under SC-CO 2 jet impacting presented: erosion and exfoliation.…”
Section: Introductionmentioning
confidence: 99%